Mothers' acceptability of using novel technology with video and audio recording during newborn resuscitation: A cross-sectional survey. - So Yeon Joyce Kong; Ankit Acharya; Omkar Basnet; Solveig Haukås Haaland; Rejina Gurung; Øystein Gomo; Fredrik Ahlsson; Øyvind Meinich-Bache; Anna Axelin; Yuba Nidhi Basula; Sunil Mani Pokharel; Hira Subedi; et al. (PLOS Digital Health, 2024)
Objective This study aims to assess the acceptability of a novel technology, MAchine Learning Application (MALA), among the mothers of newborns who required resuscitation. Setting This study took place at Bharatpur Hospital, which is the second-largest public referral hospital with 13 000 deliveries per year in Nepal. Design This is a cross-sectional survey. Data collection and analysis Data collection took place from January 21 to February 13, 2022. Self-administered questionnaires on acceptability (ranged 1-5 scale) were collected from participating mothers. The acceptability of the MALA system, which included video and audio recordings of the newborn resuscitation, was examined among mothers according to their age, parity, education level and technology use status using a stratified analysis. Results The median age of 21 mothers who completed the survey was 25 years (range 18-37). Among them, 11 mothers (52.4%) completed their bachelor's or master's level of education, 13 (61.9%) delivered first child, 14 (66.7%) owned a computer and 16 (76.2%) carried a smartphone. Overall acceptability was high that all participating mothers positively perceived the novel technology with video and audio recordings of the infant's care during resuscitation. There was no statistical difference in mothers' acceptability of MALA system, when stratified by mothers' age, parity, or technology usage (p>0.05). When the acceptability of the technology was stratified by mothers' education level (up to higher secondary level vs. bachelor's level or higher), mothers with Bachelor's degree or higher more strongly felt that they were comfortable with the infant's care being video recorded (p = 0.026) and someone using a tablet when observing the infant's care (p = 0.046). Compared with those without a computer (n = 7), mothers who had a computer at home (n = 14) more strongly agreed that they were comfortable with someone observing the resuscitation activity of their newborns (71.4% vs. 14.3%) (p = 0.024). Conclusion The novel technology using video and audio recordings for newborn resuscitation was accepted by mothers in this study. Its application has the potential to improve resuscitation quality in low-and-middle income settings, given proper informed consent and data protection measures are in place.